A Review paper on Augmented Reality - Prasad, Khushi; Khan, Rizwan (International Journal of Computer Sciences and Engineering, 2025)
This paper explores the technology of Augmented Reality by indulging in the first ever introduction to it, as well as how augmented reality has effected every individual’s day to day life now and how it will affect every individual’s day to day life in the future. It ranges from the first occurrence of augmented reality as a French author’s idea to its establishment as a technology which is not only taking over the world like a storm but will gradually make it impossible to imagine functioning without the technology of augmented reality which will be deeply rooted in our lifestyles . It is discussed how augmented reality is becoming an irreplaceable part of industries as well as people. The three approaches to augmented reality are mentioned with the concept of their working. The future of augmented reality is discussed focussing on various sectors like marketing, designing, safety and security, shopping, social media, etc.